The Geometry of Ijo Temple: Bridging Cultural Heritage and Mathematical Learning through Ethnomathematics - Olly Orva Peggy Kim Carla; Naufal Ishartono; Rizky Oktaviana Eko Putri (Universitas Muhammadiyah Surakarta, 2024)
This study explores the geometric concepts within the architecture of Ijo Temple, a significant cultural heritage site in Yogyakarta, Indonesia, through the ethnomathematics framework. Previous research has examined mathematical elements in various temples, but Ijo Temple's geometric aspects remain underexplored. Addressing this gap, the study employs an ethnographic approach to identify and analyze the temple's geometric principles, aiming to enhance mathematics education through culturally contextualized learning. Using qualitative methods, including observation, interviews, and documentation, the data were analyzed through reduction, presentation, and conclusion drawing, with findings validated by expert triangulation. The study identifies geometric sub-concepts such as planar geometry (triangles, rectangles, squares, trapezoids, circles), spatial geometry (cubes, rectangular prisms, cylinders), geometric transformations (translation, reflection, dilation), and congruence principles. The research underscores the potential of integrating cultural heritage into mathematical learning, promoting deeper engagement and understanding of mathematical concepts through the cultural context of Ijo Temple. This approach not only enriches mathematics education but also contributes to the preservation and appreciation of cultural heritage.